The decarbonization of China's agriculture - Yongfu Huang; Jingjing He (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Agriculture is one of the major greenhouse gas (GHG) emission sources in China. This paper aims to identify the key factors that have led to rising GHG emissions in China's agricultural sector in recent decades. This research allows for spatial dependence across provinces, making use of regional data from 31 provinces in mainland China. It investigates the effects of agricultural machinery, different energy types, fertilizer consumption, pesticide employment and agricultural investment on carbon emissions. The findings of this research contain significant policy recommendations for Chinese policy makers in terms of how to decarbonize China's agricultural sector, based on diverging circumstances of each region's agricultural system. It also has important implications for emission abatement policies in other developing countries sharing a similar emissions profile and regional characteristics.
Keywords: Q11; Q18; Q54; Q55; Q58; 330; agriculture; emission reductions; spatial dependence; China; Landwirtschaft; Treibhausgas; Umweltbelastung; China